Impacto do treinamento físico combinado (TFC) associado ao tratamento com Enalapril na variabilidade da pressão arterial e na disfunção renal em um modelo experimental de hipertensão arterial e menopausa - Silva, Michel Pablo dos Santos Ferreira (2020)
Introduction: Cardiovascular diseases are the main causes of mortality worldwide. Among the risk factors associated with these diseases, there is systemic arterial hypertension (HAS). HAS is considered the main cause of chronic kidney disease. In addition, the increase in blood pressure (BP) in postmenopausal women has been well documented. In this sense, it is also known that autonomic dysfunction, with increased blood pressure variability (VPA) and inflammation play important roles in the pathophysiology of HAS and its consequences on target organs such as the kidneys. On the other hand, pharmacological therapy with Enalapril and physical training have been clinically recommended for BP control. However, the association of these two types of therapies has been poorly studied, especially with regard to the impact on kidney damage in postmenopausal women. Objective: To investigate the effects of combined physical training (TFC) associated with treatment with Enalapril on VPA and on morphofunctional and inflammatory parameters in renal tissues in an experimental model of arterial hypertension and menopause. Methods: 32 spontaneously hypertensive rats (SHR) were used, distributed in 4 groups (n = 8 / group): sedentary oophorectomized (OS), sedentary oophorectomy treated with Enalapril (OSE), trained oophorectomy (OT) and trained oophorectomy treated with Enalapril (OTE). The oophorectomy was performed on the 1st day of the study and, after 5 days of pharmacological treatment and adaptation to the treadmill and training ladder, the OS group continued with placebo treatment for 8 weeks, while the other groups continued with treatment with antihypertensive medication ( 3mg / kg of Enalapril, diluted in drinking water) and / or TFC (3 days / week, 40-60% of the maximum capacity obtained in a treadmill and ladder stress test). At the end of 8 weeks, BP was recorded for VPA analysis and function analysis and inflammatory meters in renal tissue. Results: The OSE, OT and OTE groups showed a reduction in systolic BP (SBP) and diastolic BP (DBP) in relation to the OS group, while only the OT and OTE groups had lower SBP variance (VAR-SBP), standard deviation of SBP (DP-SBP) and SBP low frequency band (LF-PAS), in addition to an increase in the Alpha Index compared to the OS group. The combination of TFC and Enalapril resulted in additional benefits to the OTE group in VAR-PAS and Alpha Index. In renal assessments, there was a reduction in creatinine and IL-6 levels in the OSE, OT and OTE vs. OS, and only the OTE group showed increased creatinine clearance and IL-10 levels. The number of glomeruli was similar between the groups studied, but there was a reduction in severe interstitial tubule changes in OSE, OT and OTE vs. OS, with potentiated benefitial effect in trained groups (OT and OTE). Conclusion: TFC associated with drug therapy with Enalapril attenuated dysfunctions in vascular autonomic modulation and baroreflex sensitivity, which is probably associated with reduced inflammation and damage to renal tissue, impacting on improving renal function and reducing BP in a model hypertension and menopause.